NURSES’ KNOWLEDGE, BARRIERS, AND SOLUTIONS IN IMPLEMENTING HANDS-FREE INTRAMURAL INJECTION TECHNIQUE DURING CAESAREAN SECTION: A MIXED-METHODS STUDY - Rantung, Gilny; Kristanto, Desmond; Epang, Kori (Nursing Sciences Journal, 2025)
Sectio caesarea carries a high risk of sharp injuries that may endanger medical personnel. The Hands-Free Technique (HFT) is a method of passing sharp instruments through a neutral zone to reduce such risks. However, its understanding and application during intramural injections remain limited. Methods: A mixed-method approach with an explanatory sequential design was employed. Quantitative data were collected from 30 nurses using a questionnaire, and qualitative data were obtained through focus group discussions (FGDs) with 15 nurses. Descriptive, inferential, and thematic analyses were conducted. Results: Most respondents (53.3%) had a low level of knowledge about HFT. No significant differences were found by years of experience, prior training, or procedure frequency. The FGDs identified key barriers: limited knowledge, insufficient training and monitoring, and established routines perceived as more practical. Suggested solutions included regular practice-based training, visual aids in the workspace, supervisor accompaniment during procedures, and periodic monitoring with feedback and recognition. Discussion: These findings highlight the need for systematic interventions such as routine training, visual aids, and regular evaluations to support more consistent and safe implementation of HFT in operating rooms.  Keywords: Barrier, Hands-Free Technique, nurse knowledge, sectio caesarea, solutions